Epigenetics of Aging - Tollefsbol, Trygve O.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Revealing the molecular basis of aging has been one of the most challenging aspects of medical science, and now the epigenetics of aging is in a Renaissance phase. This seminal work covers the fascinating role of epigenetics in aging, ranging from basic epigenetic processes of aging to epigenetic drugs that may intervene in allow aging and age-related diseases. Epigenetics of Aging presents in-depth analyses of DNA methylation, histone modifications, RNA alterations, and chromosomal defects that impact the aging process. It also includes detailed essays describing the impact of epigenetics on aging, the epigenetics of age-related diseases, and future directions and perspectives on the epigenetics of aging. With chapters authored by leading researchers in the field, this seminal book on the epigenetics of aging: -Ranges from basic science to clinical practice -Describes the importance of epigenetics in numerous diseases of aging such as cancer, Alzheimer$1 (Bs disease, immune defects, and osteoporosis -Includes the role of epigenetics in premature aging diseases such as progeria -Highlights emerging aspects of epigenetics in aging, such as polycomb group genes and noncoding RNAs -Covers sirtuins, chromatin alterations, and the role of epigenetic drift in aging -Describes the impact of the environment and diet in modulating epigenetic processes during aging Epigenetics of Aging is the first book in this exponentially expanding field, and will be an indispensable source of information for those with interests in epigenetics and/or aging. This authoritative core textbook for advanced students or medical scientists and practitioners details the fascinating and revolutionary field of the epigenetics of aging and covers the most recent advances that impact the longevity of living organisms.s
Epigenetics and the Aging Process -- Epigenetics and the Aging Process -- DNA Methylation and Histone Modifications in Aging -- Age-Related Genomic Hypomethylation -- Gene-Specific Hypermethylation in Aging -- Aging and Non-sirtuin Histone Modifications -- Sirtuins and Aging -- Chromatin in Senescent Cells: A Conduit for the Anti-Aging Effects of Wnt Signaling? -- S-Adenosylmethionine: Simple Agent of Methylation and Secret to Aging and Metabolism? -- Other Epigenetic Processes and Aging -- Polycomb Group of Genes and the Epigenetics of Aging -- Chromosomal Position Effect and Aging -- Noncoding RNA for Presymptomatic Diagnosis of Age-Dependent Disease -- Impact of Epigenetics on Aging -- Telomerase Control by Epigenetic Processes in Cellular Senescence -- Telomeres, Epigenetics, and Aging -- Contributions of Tumor Suppressors to the Epigenetic Regulation of Aging Cells -- Epigenetic Drift and Aging -- Role of Epigenetics in Age-Related Long-Term Memory Loss -- Epigenetics of Age-Related Diseases -- The Epigenetics of Age-Related Cancers -- DNA Methylation and Alzheimer$1 (Bs Disease -- DNA Methylation, Age-Related Immune Defects, and Autoimmunity -- Epigenetic Silencing of Progeroid Syndromes -- DNA Methylation and Osteoarthritis -- Epigenetic Interventions and Aging -- Histone-Modifying Drugs in Aging -- Dietary Effect on Epigenetics During the Aging Process -- Environmental Effects on Age-Associated Epigenetics -- Future Directions/Perspectives -- Future Directions in Research on the Epigenetics of Aging -- Perspectives in Aging and Epigenetics -- Epigenetic Silencing of Progeroid Syndromes.s
Keywords: Medicine; Oncology; Human genetics; Toxicology; Biomedicine; Human Genetics; Cancer Research; Pharmacology/Toxicology.